2015
DOI: 10.1002/j.0022-0337.2015.79.5.tb05911.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Patient‐Centered Approach to Clinical Dental Education: A Five‐Year Reflection

Abstract: The intent of the redesign of the clinical component of the Harvard School of Dental Medicine (HSDM) curriculum from a traditional numerical procedures-based system to a patient-based comprehensive care system was to improve both patient care and student learning. The aim of this retrospective cohort study was to evaluate the outcomes of and students' perspectives on this patient-centered comprehensive care model introduced in 2009. Data were obtained from the school's Ofice of Dental Education for a study sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 11 publications
1
16
0
14
Order By: Relevance
“…For instance, Dehghan et al found that whilst students valued the opportunity to provide more comprehensive care under the group practice system, they were concerned about not being exposed to the experiences of instructors and students outside of their group, which they recognised as an advantage of the student‐centred, discipline‐based system . Similarly, Park & Howell found that fourth‐year students favoured a case‐completion system informed by the patient‐centred approach over the traditional procedure‐based system; however, they recognised the insufficient exposure to some procedures as a limitation of the former system . Park & Howell also reported that along with improving patient outcomes and student learning experiences, the case‐completion system increased the workload of clinical instructors in terms of student mentorship and patient management .…”
Section: Limitations Of Current Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Dehghan et al found that whilst students valued the opportunity to provide more comprehensive care under the group practice system, they were concerned about not being exposed to the experiences of instructors and students outside of their group, which they recognised as an advantage of the student‐centred, discipline‐based system . Similarly, Park & Howell found that fourth‐year students favoured a case‐completion system informed by the patient‐centred approach over the traditional procedure‐based system; however, they recognised the insufficient exposure to some procedures as a limitation of the former system . Park & Howell also reported that along with improving patient outcomes and student learning experiences, the case‐completion system increased the workload of clinical instructors in terms of student mentorship and patient management .…”
Section: Limitations Of Current Approachesmentioning
confidence: 99%
“…Similarly, Park & Howell found that fourth‐year students favoured a case‐completion system informed by the patient‐centred approach over the traditional procedure‐based system; however, they recognised the insufficient exposure to some procedures as a limitation of the former system . Park & Howell also reported that along with improving patient outcomes and student learning experiences, the case‐completion system increased the workload of clinical instructors in terms of student mentorship and patient management . In the same line, limitations of current CE approaches and systems (eg overemphasising student‐led dental care) largely account for the insufficient revenues that dental school clinics continue to generate, which is an issue of major concern to administrators.…”
Section: Limitations Of Current Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to assess the skills and knowledge acquired by course graduates in relation to current and future needs [10]. Although a focus on clinical training may provide more technical experience for candidates, care must be taken to fulfil other important standards, such as meeting the needs of the local community and paying attention to patient centered outcomes [11]. Collectively, these require more robust investigation to clarify their relative value and to measure the ways they are evaluated.…”
Section: Products Evaluationmentioning
confidence: 99%
“…Anabilim dallarına ait kriterler yerine getirilirken, öğrenciler arasında motivasyon sağlamak kolay olmamakla birlikte, mezuniyet sonrasındaki bağımsız çalışmalarına da sınırlı şekilde katkıda bulunur. 64 Vaka tamamlama esasına dayanan klinik eğitim modeli; 2009'da Harvard School of Dental Medicine'da uygulanmış ve eğitimde öğrencilerin ihtiyaçlarını karşılamak yerine, hasta-merkezli kapsamlı tedavi kullanılmıştır. 65,66 Bu modelde Park 64 'ın vaka sınıflama sistemi esas alınır ve öğrencilerin tamamlayacakları vakalar 6 tipe ayrılır: Yeterlik ve becerilerin değerlendirilmesini içeren klinik puanlamalar ve değerlendirmeler; öğrencilerin hünerlerini değerlendirmek için kullanılabilir ve genellikle öğrencileri hastalarla iletişimleri ve klinik performanslarına göre değerlendiren klinik eğitmenlerin varlığında yapılır.…”
unclassified